SEKOLAH ISLAM: SEBUAH TINJAUAN IDEOLOGIS DAN PENDIDIKAN HUMANIS PADA SEKOLAH DASAR ISLAM CREATIVE BANJARBARU - Willy Ramadan; Yahya Mof (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2022)
This article describes the educational ideology of the founder or initiator of SD Islam Creative and how to implement humanist values in learning. This article is the result of field research with a qualitative approach. The multiplication data in this study was obtained from 4 informants consisting of 1 founder, 1 principal and 2 teachers. To explore the first objective of the research, the informants have been determined by the researcher or known as the purposive sampling technique, while for other informants using the snowball sampling technique. The instrument used in this study was conducted by interviewing informants, making observations in the field, and also documents. The stages in the research consist of the pre-field stage, the field work stage, and the data analysis stage. The finding states that the educational ideology of the founders is liberalism with an approach to educational philosophies. While the implementation of humanist values in learning can be seen in 4 things are (1) the application of multiple intelligences as a basic program or learning method for students; (2) Giving children the freedom to express and learn with the natural surroundings, so that learning becomes fun for students; (3) Shaping children's character through programs such as Islam, independence, and honesty; (4) Students are educated in a humanistic way.